Interplay among Membrane-Bound Lytic Transglycosylase D1, the CreBC Two-Component Regulatory System, the AmpNG-AmpD(I)-NagZ-AmpR Regulatory Circuit, and L1/L2 β-Lactamase Expression in Stenotrophomonas maltophilia - Huang, Yi-Wei (Antimicrob Agents Chemother, 2015)
Lytic transglycosylases (LTs) are an important class of enzymes involved in peptidoglycan (PG) cleavage, with the concomitant formation of an intramolecular 1,6-anhydromuramoyl reaction product. There are six annotated LT genes in the Stenotrophomonas maltophilia genome, including genes for five membrane-bound LTs (mltA, mltB1, mltB2, mltD1, and mltD2) and a gene for soluble LT (slt). Six LTs of S. maltophilia KJ were systematically mutated, yielding the ΔmltA, ΔmltB1, ΔmltB2, ΔmltD1, ΔmltD2, and Δslt mutants. Inactivation of mltD1 conferred a phenotype of elevated uninduced β-lactamase activity. The underlying mechanism responsible for this phenotype was elucidated by the construction of several mutants and determination of β-lactamase activity. The expression of the genes assayed was assessed by quantitative reverse transcriptase PCR and a promoter transcription fusion assay. The results demonstrate that ΔmltD1 mutant-mediated L1/L2 β-lactamase expression involved the creBC two-component regulatory system (TCS) and the ampNG-ampD(I)-nagZ-ampR regulatory circuit. The inactivation of mltD1 resulted in mltB1 and mltD2 upexpression in a creBC- and ampNG-dependent manner. The overexpressed MltB1 and MltD2 activity contributed to the expression of the L1/L2 β-lactamase genes via the ampNG-ampD(I)-nagZ-ampR regulatory circuit. These findings reveal, for the first time, a linkage between LTs, the CreBC TCS, the ampNG-ampD(I)-nagZ-ampR regulatory circuit, and L1/L2 β-lactamase expression in S. maltophilia.